COMMUNICATING ENVIRONMENTAL RESPONSIBILITY: CSR BENIH BAIK AND THE CONSTRUCTION OF GARUDA INDONESIA’S GREEN AIRLINE IMAGE - Dela Anjelawati; Dinda Amaris (Journal of Social Political Sciences, 2025)
The intensification of global environmental crises has compelled the aviation sector to adopt Corporate Social Responsibility (CSR) not merely as a philanthropic obligation but as a vital strategic communication tool for reputation management. This study critically analyzes the "Benih Baik" initiative by Garuda Indonesia to understand how environmental CSR is mobilized to construct a "Green Airline" image. Integrating perspectives from Media Ecology, Stakeholder Engagement, and Greenwashing theories, the research explores the tension between symbolic communication and substantive impact. The study employs a qualitative single-case methodology, utilizing data triangulation from in-depth interviews with corporate communication practitioners, extensive documentation review, and digital media observations during the 2024–2025 period. The analysis reveals that Garuda Indonesia executes a systematic communication strategy characterized by "identity construction" positioning the airline as a guardian of national nature—and "visual persuasion," where digital content of mangrove planting serves as primary evidence of responsibility. Additionally, participatory messaging is used to foster a sense of collective ownership among stakeholders. However, a critical gap emerges: while the campaign succeeds in generating high visibility and emotional resonance, it notably lacks the disclosure of measurable ecological data, such as tree survival rates or quantified carbon offsets. This absence of verifiable outcomes suggests a reliance on "symbolic legitimacy," leaving the airline vulnerable to potential greenwashing critiques. The study concludes that sustainable reputation building in aviation requires a paradigm shift from performing visibility to proving ecological accountability, offering strategic insights for airlines operating in developing economies